Antibacterial Activity and Tlc-Biotography Profile of the Ethyl Acetat Fraction of Asian Pigeonwings Flower (Clitoria ternatea) against Escherichia coli - Ari Susilowati; Rizkya Suhardo Putri; Widya Mudyantini (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
Infectious diseases are diseases caused by the presence of microorganisms that enter and develop in the body, causing several clinical symptoms and signs. One of the infectious diseases is diarrhea caused by Escherichia coli. There are many potential herbal plants as alternative antibacterial antibiotics, one of which comes from the Asian pigeonwings flower (Clitoria ternatea). This study aims to determine the antibacterial activity of the ethyl acetate fraction of pigeonwings flower, phytochemical compounds and its TLC-bioautography profile. The antibacterial compound of pigeonwings flower was extracted by maceration using ethanol and then fractionated by ethyl acetate and made solutions with concentrations of 5, 10, 20, and 40%, respectively. The experiment was carried out with 3 replications using the well diffusion method and followed by TLC-bioautography to determine the TLC-bioautography profile. Phytochemical compounds of pigeonwings flower were determined by thin layer chromatography (TLC). Antibacterial activity data were analyzed using the One Way ANOVA and continued with the Tukey HSD 5% through SPSS. The ethyl acetate fraction of pigeonwings flower had the best antibacterial activity at a concentration of 40% with an inhibition zone diameter of 11.54 mm. The diameter of the inhibition zone showed significantly different in each concentration and it can be said that the ethyl acetate fraction of pigeonwings flower was able to inhibit the growth of E. coli. The phytochemical compounds contained in the ethyl acetate fraction of pigeonwings flower are flavonoids and alkaloids with flavonoids being the most active compounds in inhibiting the growth of E. coli.